2006
DOI: 10.1055/s-2006-925149
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Band Ligation of Bleeding Dieulafoy Lesions: The Best Therapeutic Strategy

Abstract: Dieulafoys lesion is a vascular lesion that is widely recognized as a persistently en− gorged, tortuous artery in the muscularis mucosa which is not associated with in− flammation or atherosclerosis. The inci− dence of this lesion in patients with upper gastrointestinal bleeding has been estima− ted to be between 0.3 % and 6.7 %. Clinical− ly, these lesions manifest as massive gas− trointestinal hemorrhage, with no preced− ing symptoms. If the lesion is not treated, patients continue to bleed intermittently ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 3 publications
1
10
0
7
Order By: Relevance
“…5,6 With the advances in endoscopic techniques for locating and managing a bleeding site, endoscopic treatment has replaced surgery as the standard diagnostic and therapeutic approach for bleeding DLs. 5,7 The rate of hemostasis with endoscopic treatment is known to reach 75% to 100%, 1,5,6,[8][9][10][11][12][13][14][15][16][17][18][19] and a good long-term prognosis after endoscopic treatment has been proved to date. 1,6,9,14,15 Studies have shown that mechanical endoscopic methods, such as endoscopic hemoclip placement (EHP) and endoscopic band ligation (EBL), are more effective treatments than other endoscopic methods, such as injection and thermal therapy.…”
mentioning
confidence: 99%
“…5,6 With the advances in endoscopic techniques for locating and managing a bleeding site, endoscopic treatment has replaced surgery as the standard diagnostic and therapeutic approach for bleeding DLs. 5,7 The rate of hemostasis with endoscopic treatment is known to reach 75% to 100%, 1,5,6,[8][9][10][11][12][13][14][15][16][17][18][19] and a good long-term prognosis after endoscopic treatment has been proved to date. 1,6,9,14,15 Studies have shown that mechanical endoscopic methods, such as endoscopic hemoclip placement (EHP) and endoscopic band ligation (EBL), are more effective treatments than other endoscopic methods, such as injection and thermal therapy.…”
mentioning
confidence: 99%
“…[20][21][22][23] EBL varisiyel üst GİS kanamalarında rutin uygulanan bir prosedürdür. İlk kez Brown ve arkadaş-ları [15] DL'de EBL ile kanama kontrolünü sağladıkları-nı 1994 yılında rapor etmişlerdir.…”
Section: Discussionunclassified
“…İlk kez Brown ve arkadaş-ları [15] DL'de EBL ile kanama kontrolünü sağladıkları-nı 1994 yılında rapor etmişlerdir. Yine Valera ve arkadaşları [20] DL kanaması nedeniyle EBL uyguladıkları 4 hastalarında band ligasyonu ile başarılı hemostaz sağladıklarını rapor etmişler, hastalarının hiçbirinde tekrar kanama görülmediğini belirtmişlerdir. EBL uygulaması sonrasında 14-21 günde iyileşen sığ, temiz tabanlı, ülserler görülebilmektedir.…”
Section: Discussionunclassified
“…Mechanical endoscopic treatment, especially band ligation, has been suggested to achieve better primary hemostasis than injection therapy alone. Furthermore, the risk of rebleeding has been shown to be much lower with mechanical treatment compared to injection treatment (16,17). In addition, endoscopic band ligation is technically easier than hemoclip applications and injection methods, especially when the esophagogastric junction or the posterior wall of the proximal body of the stomach is involved.…”
Section: Discussionmentioning
confidence: 99%